Pengaruh DBH, DAU, DAK Terhadap Bd Di Kota, Provinsi Jawa Timur Tahun 2014-2021 - Novita Wulandari; Rahmad Wahyu Hidayat; Moh. Khoirul Fuddin (Universitas Islam Kadiri, 2023)
The purpose of this study was to determine the effect of balancing funds, including revenue-sharing funds (ISF), general allocation funds (GAF), and special allocation funds (SAF) on regional expenditure per city in the city of East Java Province in 2014-2021. The analysis tool used is panel data regression. The results of the study show that the variables of profit-sharing funds, general allocation funds, and special allocation funds have a positive and significant influence on regional spending in the City of East Java Province.